Distribution of Salvadora oleoides Decne. In Arid Regions of Northwestern India – An Overview - JANGRA, ANAMIKA; MAIKHURI, SANDEEP; BARTHWAL, SANTAN; PANDEY, SHAILESH; SINGH, G.; MEENA, RAJENDRA K; KANT, RAMA; BHANDARI, MANEESH S. (Indian Forester, 2023)
Not Abstract.